Facile route for large-scale synthesis of reversible thermochromic polydiacetylene/zinc(II) assemblies: The effect of zinc(II) precursors - Rueangsuwan J. (2023)
Polydiacetylenes (PDAs) are stimuli-responsive polymers that have shown potential for colorimetric detection of various stimuli. Commercially available PDAs often exhibit irreversible blue-to-red thermochromism, limiting their applications. In this study, we develop a facile method, involving the co-assembly of zinc (Zn2+) ions and PDAs in an aqueous medium, for creating reversible thermochromic materials. We have found that the Zn2+ precursors play a crucial role on achieving a reversible thermochromism. The PDA/Zn2+ assemblies prepared from Zn(CN)2 and Zn(CH3COO)2 exhibit reversible thermochromism whereas other Zn2+ precursors such as ZnCl2, Zn(NO3)2 and ZnSO4 do not yield reversibility. The reversible thermochromic PDA/Zn2+ assemblies can be synthesized via the solution mixing method in ambient conditions, making them suitable for large-scale production. The color-transition temperature can be tuned from 60 to 120 °C by changing PDA side chains. The synthesis of reversible thermochromic PDA/Zn(CN)2 assemblies in the liquid phase allows the fabrication of smart inks, sprayed coatings, and nanofibers, extending their fields of applications.